PERKEMBANGAN TEKNOLOGI DAN PENTINGNYA LITERASI INFORMASI UNTUK MENDUKUNG KETAHANAN NASIONAL - subarjo, abdul haris (Sekolah Tinggi Teknologi Adisutjipto, 2017)
Technology makes it easy to get various information. Various sources can be easily accessed. The speed of providing up-to-date information on social media has become one of the necessities of late. Indirectly assist the dissemination of various information in Indonesia. Technological updates make no geographical barrier, norms, ethical boundaries, less visible. The various facilities offered will have a higher value if the truth of the information can be accounted for. On the other hand as a human being still has inherent human rights, as well as citizens. Therefore, in accessing, utilizing and disseminating various information obtained required a filter called information literacy. Anyone who has had information literacy does not easily disseminate information without first checking the truth. Distribution of various information that is correct and polite will make the recipient of information reasoning well so it is not easy to be hooked to do something unsettling. Thus, information literacy is essential to support national resistance.Keywords: technology, information literacy, national resistance.Â